The temperature dependence of the inelastic scattering time in InGaN grown by MOVPE - Yildiz, A.; Kasap, M. (Физика низких температур, 2010)
Low temperature electrical measurements of the resistivity, the Hall effect and the magnetoconductivity were performed on an InGaN sample having an electron concentration far above the critical value for the metalinsulator transition. Weak localization effect and two-band model were used to analyze the magnetoconductivity data. The temperature dependence of the inelastic scattering time was extracted from the magnetoconductivity data at low temperatures. It was found that the inelastic scattering time is proportional to T⁻¹.⁶³, suggesting that electron–electron interactions are dominant.